Assessment of Maternal-Infant-Bonding between mothers and their babies with a cleft lip - Nienaber, Elzette (My University, 2017)
Currently there is no literature exploring how having a child with a cleft lip with or without a cleft palate affects the maternal-infant bonding in a South African context. This study aimed to describe bonding between mothers and their affected infants and to determine whether demographic factors are associated with bonding impairment. Thirty two mothers with affected children were recruited from two clinics at Johannesburg State Hospitals. The Postpartum Bonding Questionnaire was used to establish bonding impairment in this group. The results indicated that 4 (12.5%) of the mothers had some impaired bonding while the majority of mothers 28 (87.5%) had normal bonding. Some mothers displayed a degree of anxiety concerning planned reconstructive surgery. In conclusion, we found that having a child with a cleft lip does not significantly influence maternal-infant bonding, however investigations with larger cohort is needed for further clarification.
A research report (in the format of a “submissible” paper) submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Genetic Counselling) Johannesburg, 2017.
Keywords: Maternal-Infant-Bonding; Cleft Lip